2010
DOI: 10.1007/bf03346594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of double pituitary adenomas in a surgical series: Clinical, histological and genetic features

Abstract: The prevalence of DPA observed in our unselected surgical series is not negligible (2.6%). Furthermore, the evaluation of the treatment outcome would suggest that the clinical management of DPAs requires a careful diagnostic approach and follow- up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 34 publications
1
39
2
Order By: Relevance
“…Magri et al (9) reported that the incidence of double pituitary adenomas in patients who chose not to undergo surgery was 2.6%. Double or multiple pituitary adenomas, and clearly separated adenomas confirmed by preoperative imaging or intraoperative exploration in particular, are considerably rare.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Magri et al (9) reported that the incidence of double pituitary adenomas in patients who chose not to undergo surgery was 2.6%. Double or multiple pituitary adenomas, and clearly separated adenomas confirmed by preoperative imaging or intraoperative exploration in particular, are considerably rare.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients were aged 41.5-45.5 years. On the basis of preoperative, intraoperative and postoperative evaluations, 42 patients were diagnosed with clearly separated double pituitary adenomas (1-4,8,10-14,17-25), 36 patients with contiguous pituitary adenomas (6)(7)(8)(9)11,12,14,(26)(27)(28)(29), and 3 patients with 3 pituitary adenomas (11,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations